INKONSISTENSI PENERAPAN KONSEP PENYERTAAN (MEDEPLEGEN) BERDASARKAN PERATURAN HUKUM DI INDONESIA - Waruwu, Samueli; Yunara, Edi; Rizky, Fajar Khaify (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This research examines the inconsistency in the application of the concept of participation (medeplegen) based on legal regulations in Indonesia. Indonesia as a state of law (rechtsstaat) requires consistency in the application of legal norms, including criminal law. However, in practice, there are often inconsistencies in the application of participation regulations as stipulated in Article 55 of the Criminal Code (KUHP) in conjunction with Article 20 of the National Criminal Code (KUHP Nasional) of 2023. This study uses normative legal research methods with statutory and case approaches. The results of the research indicate that first, the juridical provisions regarding the concept of participation in the criminal law system include several forms: pleger (person who commits), doen pleger (person who causes another to commit), medepleger (person who participates in committing), and uitlokker (person who incites). Second, the inconsistency in applying the concept of participation occurs due to differences in interpretation between law enforcers, lack of clear guidelines in distinguishing forms of participation, and the transition period between the old Criminal Code and the National Criminal Code of 2023. This research recommends the need for technical guidelines from the Supreme Court and intensive socialization regarding the implementation of participation provisions in the new national criminal law. Keywords: Participation, Medeplegen, Criminal Law, Inconsistency, National Criminal Code Abstrak: Penelitian ini mengkaji inkonsistensi penerapan konsep penyertaan (medeplegen) berdasarkan peraturan hukum di Indonesia. Indonesia sebagai negara hukum (rechtsstaat) menghendaki konsistensi dalam penerapan norma hukum, termasuk hukum pidana. Namun dalam praktiknya, seringkali terjadi inkonsistensi dalam penerapan regulasi penyertaan sebagaimana diatur dalam Pasal 55 Kitab Undang-Undang Hukum Pidana (KUHP) juncto Pasal 20 KUHP Nasional Tahun 2023. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan pendekatan kasus. Hasil penelitian menunjukkan bahwa pertama, ketentuan yuridis konsep penyertaan dalam sistem hukum pidana mencakup beberapa bentuk: pleger (orang yang melakukan), doen pleger (orang yang menyuruh melakukan), medepleger (orang yang turut serta melakukan), dan uitlokker (orang yang menganjurkan). Kedua, inkonsistensi penerapan konsep penyertaan terjadi karena perbedaan penafsiran antaraparat penegak hukum, tidak adanya pedoman yang jelas dalam membedakan bentuk-bentuk penyertaan, serta masa transisi antara KUHP lama dengan KUHP Nasional 2023. Penelitian ini merekomendasikan perlunya pedoman teknis dari Mahkamah Agung dan sosialisasi intensif mengenai implementasi ketentuan penyertaan dalam hukum pidana nasional yang baru. Kata Kunci: Penyertaan, Medeplegen, Hukum Pidana, Inkonsistensi, KUHP Nasional